1990
DOI: 10.1002/etc.5620090109
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral responses of marked snails as indicators of water quality

Abstract: Behavioral responses of the common stream‐dwelling operculate snail Elimia clavaeformis were used to provide information about streamwater quality in in situ tests. These snails were found to be advantageous for such tests because they can be collected easily, individually marked, and transferred to other stream sites for release and recapture experiments. In noncontaminated stream sites, Elimia tended to disperse upstream. The rate of net movement was variable, but typically ranged from 0.5 to 5 m/d. Water ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…Isolation from the surrounding environment was observed in bivalve molluscs (Davenport 1977) but also in prosobranch species (Burris et al 1990). The avoidance of a contaminated environment during reproduction or recruitment has been reported as a protective behaviour in some species.…”
Section: Changes In Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation from the surrounding environment was observed in bivalve molluscs (Davenport 1977) but also in prosobranch species (Burris et al 1990). The avoidance of a contaminated environment during reproduction or recruitment has been reported as a protective behaviour in some species.…”
Section: Changes In Behaviourmentioning
confidence: 99%
“…Other studies have shown that intoxication may negatively affect the individual ability to escape from predators (Ward et al 1976) or to swim or move (Capaldo 1987, Burris et al 1990, Villar et al 1993. At the community level, these alterations may affect predator-prey relationships.…”
Section: Changes In Behaviourmentioning
confidence: 99%
“…However, despite its high ecological relevance, there is still scarce information on the effects of discontinuous exposure on behaviour (Alonso and Camargo 2004;Azevedo-Pereira et al 2011). Among behavioural endpoints, those related to movements (e.g., time to start normal activity, swimming, sliding, drift, time to reach food) are important from an ecological point of view (Burris et al 1990;Golding et al 1997;Cheung et al 2002;Camargo 2004, 2009;Cold and Forbes 2004;Beketov and Liess 2008). This kind of behaviour is related to relevant functions for animal fitness, such as the ability to avoid predators and pollutants, reproduce, search for resources, and avoid environmental stressors.…”
mentioning
confidence: 98%
“…Poor food availability can potentially provide strong motivation for snail movement (Burris et al, 1990;Dillon, 2000). High activity could also suggest that snails were trying to escape CYN contaminated water, however, this does not explain the high activity in the controls.…”
Section: Snail Behaviourmentioning
confidence: 99%